Learning Indonesian History of the Colonial Period: An Ecopedagogical Perspective - Wattimury, Samuel Michael; Abrar, Abrar; Kurniawati, Kurniawati (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This article aims to analyze and describe the implementation of ecopedagogic-based history learning in the Colonial Indonesian History course. This research uses this qualitative research method, and the data analysis model used is an interactive analysis model. Starting from the stages of data condensation, data presentation, and conclusion and verification. The results showed that the history learning process carried out in sixteen face-to-face meetings had been carried out by integrating elements or main pillars in ecopedagogic-based learning, namely historical environmental literacy, cultural literacy, and utilization. This research is relevant to Bloom's competency domain, namely the competency domain of knowledge, attitudes, and skills. Previous research related to ecopedagogy only focused on the natural environment and its relevance to biology and social studies learning. Meanwhile, this research focuses on historical environments such as forts, museums, and monuments and their relevance to learning history. Ecopedagogic-based history learning is one of the solutions to monotonous history learning and is associated with the negative connotation that history learning is a boring memorization lesson.